Estimation of Concentrations of Phenolic Compounds in Peppers Found in the Brazilian Market by the Folin-Ciocalteu Method - Ravasi Stefano Simionato, Eliane Maria; Numes de Mello, Bruno Garcia; Spadotto, Inglaesa Carolina; Daiuto, Erica Regina [UNESP]; Vieites, Rogerio Lopes [UNESP]; Smith, Robert E. (Bentham Science Publ, 2015)
There is much diversity in the peppers in the genus Capsicum. They are considered to be good sources of vitamins C and E, as well as phenolic compounds. The present study evaluated the concentrations of total phenolics in 19 different cultivars from five species of peppers. The highest concentration was in the malaguetas (C. frutescens) with 2.54 mg gallic acid equivalents per 100g (mg GAE 100 g(-1)), followed by the biquinho (C. chinense) with 1.74 GAE 100 g(-1) and the bhut jolokia (C. chinense) with 1.24 mg GAE 100 g(-1). The lowest concentration was found in Americana (C. annuum) and cambuci verdi (C. chinense), each of which had 0.10 mg GAE 100 g(-1).
Keywords: Biquinho; Capsicum; malagueta; phenolics; peppers.